Two days in summer - Chaplin, Michael; Miller, Nigel; Hill, Jim; Longman (Firm) ([S.l.] : Longman ELT Video, 1986)
Eddy comes to London to do a college project, picks up the keys from his sister's office and end up being questioned by the security service
cassete 1 : Units 1 - 8 (28 mins.), cassette 2 : units 9 - 15 (24 mins.
Intended audience : Students of English at elementary level
Copy available in DVD format
Cast : Jonathan Caplan, David Beale, Yolanda Vasquez
Library's holdings : cassette 2
Keywords: English language -- Study and teaching